Audit Tenure, Size of Public Accounting Firm, Audit Fee, and Integrity of Financial Statements: Empirical Evidence from Indonesian Listed Mining Firms - Putri Nurmala; Dessy Bustanti; Akhmad Sigit Adiwibowo (Universitas Muhammadiyah Semarang, 2021)
This study aimed to determine the effect of audit tenure, size of accounting public firm, and audit fee for the integrity of the financial statements. The method used in this study is quantitative with a causal associative type. The object of research is mining companies listed on the Indonesia Stock Exchange in the period 2016-2018. The population in this study were all companies listed on the Indonesia Stock Exchange as many as 496 companies and the samples obtained were 15 companies. Data analysis methods used were multicollinity test, overall model test , the feasibility test of the regression model, the coefficient of determination test, the logistic regression analysis test, the classification matrix test and the simultaneous test. The results showed that audit tenure, size of accounting public firm, and audit fee simultaneously had a significant effect on the integrity of financial statements. Partially audit fee have a significant effect on the integrity of financial statements. The effect of audit fee on the integrity of financial statements is positive as evidenced by the results of positive regression values. Meanwhile, audit tenure and size of accounting public firm partially no significant effect on the integrity of financial statements.